Including students with disabilities in Learning Communities - Silvia Molina; Oriol Ríos (Psychology, Society & Education, 2010)
Learning Communities is a project for school transformation theobjective of which is to achieve high quality education for all students, avoiding all type of segregation due to students’ level of attainment or other characteristics, and any type of differentiation or acritical adaptation of the curriculum, which may lead to unequal learning results. Students with disabilities have traditionallybeen subject to these types of practices which, nevertheless, have dubious results as far as the learning and social integration of these students is concerned. It is necessary to identify educational strategies which respond to the specific needs of these students within the framework of the same educational environment and the same learning objectives, as is being claimed from the inclusive education perspective. Starting from these premises, in this article we review the Learning Communities model as a school model which contributes to the inclusion of students with disabilities. Firstly, we will define the term “disability” and its educational implications as compared to other concepts which have also been usedin this field. Secondly, we describe some of the characteristics of the learning communities in relation to inclusive education and we focus particularly on the way in which the learning communities approach responds to the specific educational needs of students with disabilities. Finally, we will focus on a specific classroom practice, the interactive groups, and its contributions to the inclusion of students with disabilities.